Influence of Heat Treatment After Arc Discharge Route on Structure and Loading Capacity of SBA-15 Encapsulated By Iron Particles - Ulfa, M; Saraswati, T E; Mulyani, B (KnE Life Sciences, 2019)
For the first time, the influence of heat treatment on the structure of SBA-15 encapsulated iron particle has been investigated after arc discharge methods. Molecular sieve silica SBA-15 was prepared by self-assembly route using block copolymer P123 as soft templating agent and tetraethoxysilane as silica precursor involving acid treatment. Arc discharge route was followed by heat-treatment of SBA-15 for 4 h at 400, 700 and 900 ∘C. The change of sample structure was studied by X-ray diffraction, scanning electron microscopy and nitrogen adsorption-desorption techniques, VSM and FTIR. It is found that after arc discharge step, the magnetic properties of SBA-15 encapsulated iron particle reached stable crystal at high temperature. In the other way, the massive structural change in a significant part of SBA-15 encapsulated iron particle during high temperature had an impact on the decreased surface area, total pore volume, and post size distribution. The loading capacity performance of SBA-15 encapsulated iron particle was investigated by ibuprofen molecule impregnation as a drug model. The result showed that high-temperature treatment of SBA-15 encapsulated iron particle decreased the loading capacity which was firmly related to the shrinkage of mesoporous nanopipe of SBA-15.